Tehrangeles dreaming : intimacy and imagination in Southern California's Iranian pop music - Hemmasi, Farzaneh (Duke University Press, 2020)
Los Angeles, called Tehrangeles because it is home to the largest concentration of Iranians outside of Iran, is the birthplace of a distinctive form of postrevolutionary pop music. Created by professional musicians and media producers fleeing Iran's revolutionary-era ban on “immoral” popular music, Tehrangeles pop has been a part of daily life for Iranians at home and abroad for decades. In Tehrangeles Dreaming Farzaneh Hemmasi draws on ethnographic fieldwork in Los Angeles and musical and textual analysis to examine how the songs, music videos, and television made in Tehrangeles express modes of Iranianness not possible in Iran. Exploring Tehrangeles pop producers' complex commercial and political positioning and the histories, sensations, and fantasies their music makes available to global Iranian audiences, Hemmasi shows how unquestionably Iranian forms of Tehrangeles popular culture exemplify the manner in which culture, media, and diaspora combine to respond to the Iranian state and its political transformations. The transnational circulation of Tehrangeles culture, she contends, transgresses Iran's geographical, legal, and moral boundaries while allowing all Iranians the ability to imagine new forms of identity and belonging. -- présentation de l'éditeur